The carbohydrate metabolism and expression of carbohydrate-active enzyme genes in Aspergillus luchuensis fermentation of tea leaves - Li, Ruoyu; Wang, Teng; Bo, Nianguo; Wang, Qi; Chen, Qiuyue; Liang, Zhengwei; Guan, Yanhui; Jiang, Bin; Ma, Yan; Zhao, Ming (Frontiers in Microbiology, 2024)
Introduction Carbohydrates, which make up 20 to 25% of tea beverages, are responsible for their flavor and bioactivity. Carbohydrates of pu-erh tea change during microbial fermentation and require further research. In this study, we examined the carbohydrate metabolism and expression of carbohydrate-active enzyme genes during the fermentation of tea leaves with Aspergillus luchuensis. Methods Widely targeted metabolomics analysis, high-performance anion-exchange chromatography measurements, and transcriptomics were used in this study. Results After fermentation, the levels of soluble sugar, hemicellulose, lignin, eight monosaccharides, and seven sugar alcohols increased. Meanwhile, the relative contents of polysaccharides, D-sorbitol, D-glucose, and cellulose decreased. High expression of 40 genes encoding 16 carbohydrate enzymes was observed during fermentation (FPKM>10). These genes encode L-iditol 2-dehydrogenase, pectinesterase, polygalacturonase, α-amylase, glucoamylase, endoglucanase, β-glucosidase, β-galactosidase, α-galactosidase, α-glucosidase, and glucose-6-phosphate isomerase, among others. Discussion These enzymes are known to break down polysaccharides and cell wall cellulose, increasing the content of monosaccharides and soluble sugars.